UPAYA PENINGKATAN MINAT BACA DI LINGKUNGAN SEKOLAH DAN MASYARAKAT DI SMA NEGERI 1 JEBUS PADA TAHUN 2019 - Kusmiati Kusmiati (JEM Jurnal Ekonomi dan Manajemen, 2020)
The library is the heart of the formal education world, so the library needs to be arranged in such a way as to become a space or place that is interesting and fun for all readers. Informing or organizing a library, it is necessary for the cooperation of all school residents to obtain the expected results. This paper seeks to explain the efforts of schools and libraries in increasing student and community interest in reading. In order to attract students to visit the library of Jebus 1 Public High School, librarians package the library in such a way as to give the name "Depati Bahrin reading park" with the aim to arouse interest, increase references by procuring new books, widening space and spatial planning, working with stakeholders, establishing gazebos, forming natural classes, procuring information literacy galleries, procuring mobile literacy with "keraca" (reading baskets), adding supporting libraries and thematic libraries, and adding facilities and infrastructure including security gates, barcodes, air conditioners, etc. From the various efforts that have been made by the school and librarians, there has been an increase in visits from both students and the community, this library also gained achievements at the local, regional and national level.